2014
DOI: 10.1016/j.chb.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Social desirability is the same in offline, online, and paper surveys: A meta-analysis

Abstract: The aim of this meta-analysis was to compare social desirability scores between paper and computer surveys. Subgroup analyses were conducted with Internet connectivity, level of anonymity, individual or group test setting, possibility of skipping items, possibility of backtracking previous items, inclusion of questions of sensitive nature, and social desirability scale type as moderators. Subgroup analyses were also conducted for study characteristics, namely the randomisation of participants, sample type (stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(134 citation statements)
references
References 79 publications
2
129
0
3
Order By: Relevance
“…In the field of epidemiology, it has been shown that respondents taking an online questionnaire do not systematically differ from those surveyed by more traditional means in terms of age, gender, income, education or health status (van Gelder, Bretveld, & Roeleveld, 2010). The issue of differences in social desirability was addressed in a recent meta-analysis encompassing 16,700 participants (Dodou & de Winter, 2014). That study found no differences in social desirability scores in paper and computer surveys.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of epidemiology, it has been shown that respondents taking an online questionnaire do not systematically differ from those surveyed by more traditional means in terms of age, gender, income, education or health status (van Gelder, Bretveld, & Roeleveld, 2010). The issue of differences in social desirability was addressed in a recent meta-analysis encompassing 16,700 participants (Dodou & de Winter, 2014). That study found no differences in social desirability scores in paper and computer surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Social desirability may especially be at play when it comes to disclosing illegal activities such as using a mobile phone while driving or when indicating one's risk awareness (e.g., Q18). However, anonymity, as was adopted in the present survey, may resolve some of these concerns (Dodou and de Winter 2014). For example, Lajunen and Summala (2003) found that in a public setting (i.e., when applying for a driving instructor training course as part of the entrance examination), not one of about 50 respondents admitted having been driving when over the legal blood alcohol limit, whereas 23% confessed this illegal behavior in a private setting in which confidentiality was stressed.…”
Section: Limitations and Recommendationsmentioning
confidence: 97%
“…Additionally, given the study's strategy of obtaining information via self-report as opposed to objective measures, it has the potential of leading to ascertainment bias, specifically responder reporting bias. Where this was avoided to the best extent possible by ensuring confidentiality and providing both in-person and lap-top interviewing methods, subjects have a natural tendency to answer questions in a way that allows them to align with cultural beliefs [21]. This likely lead to a decrease in the overall reported number of undesired pregnancies and in increase in the overall reported contraception use, and therefore our results likely underestimate the true unintended pregnancy rate.…”
Section: Discussionmentioning
confidence: 56%